Projecting Saudi sectoral electricity demand in 2030 using a computable general equilibrium model - Salaheddine Soummane (Elsevier, 2022)
Electricity demand in Saudi Arabia is undergoing unprecedented changes following the implementation of efficiency measures and energy price reforms. These changes raise uncertainties about the potential trajectory of long-term electricity demand. Thus, this study uses a computable general equilibrium model to project sectoral electricity demand in Saudi Arabia through 2030. We project that growth in total Saudi electricity demand will significantly decelerate over the coming decade compared with historical trends. In our reference scenario, this demand reaches 365.4 terawatthours (TWh) by 2030. However, our sectoral decomposition shows large disparities across sectors. Demand is projected to grow more rapidly in the industrial and services segments than in the residential sector. We also simulate four additional scenarios for domestic electricity price reforms and efficiency policies. Successfully implementing these measures may result in significant energy savings. Aligning Saudi electricity prices with the average electricity price among G20 countries can reduce total electricity demand by up to 71.6 TWh in 2030. Independently enforcing efficiency policies can reduce total electricity demand by up to 118.7 TWh. Moreover, alternative policy scenarios suggest that the macroeconomic gains from energy savings can alleviate some of the Saudi energy system's burden on public finance.